Impact of Discretionary Accrual Earnings Management on Firm Value of Listed Consumer Goods Firms in Nigeria - Isiaka, Taiwo Muideen; Kighir, Apedzan Emmanuel; Yusuf, Ismaila (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
This study examined the impact of discretionary accrual earnings management on the firm value of listed consumer goods firms in Nigeria. The study adopted a longitudinal panel research design, selecting a sample of sixteen (16) firms through a purposive sampling technique from the population of twenty-one consumer goods firms listed in the Nigerian Exchange Group (NGX) as of 31st December 2022. Earnings management was proxied using the absolute value of discretionary accruals via a modified Jones model, while Tobin's Q ratio served as the measure for firm value. Data spanning 2013 to 2022 was sourced from audited annual financial statements of the sampled firms. Various analytical methods, including descriptive analysis, correlation analysis, and multiple regression techniques, were employed to analyze the dataset. The results revealed that discretionary accrual earnings management has a positive and significant impact on the firm value of listed consumer goods firms in Nigeria. Considering these findings, the study recommends that policy makers should strengthen frameworks to detect and deter excessive or deceptive earnings management practices that could mislead investors and distort market perceptions. Therefore, effective frameworks are essential to ensure that earnings management practices adhere to ethical standards.